Synthesis of New Cisplatin Derivatives from Bile Acids - Seroka, Barbara; Łotowski, Zenon; Hryniewicka, Agnieszka; Rárová, Lucie; R Sicinski, Rafal; M Tomkiel, Aneta; W Morzycki, Jacek (Molecules (Basel, Switzerland), 2020)
A series of bile acid derived 1,2- and 1,3-diamines as well as their platinum(II) complexes were designed and synthesized in hope to get a highly cytotoxic compound by the combination of two bioactive moieties. All complexes obtained were subjected to cytotoxicity assays in vitro and some hybrid molecules showed an expected activity.
Keywords: Cell Survival; Inhibitory Concentration 50; Platinum Compounds; Bile Acids and Salts; MFC-7 buňky; Humans; HeLa buňky; lithocholic acid; cisplatina; Cisplatin; žlučové kyseliny a soli; hyodeoxycholic acid; inhibiční koncentrace 50; lidé; proliferace buněk; molekulární struktura; Human Umbilical Vein Endothelial Cells; sloučeniny platiny; Drug Design; Molecular Structure; steroidal diamines; HeLa Cells; deoxycholic acid; endoteliální buňky pupečníkové žíly (lidské); Cell Proliferation; racionální návrh léčiv; platinum(II) complexes; bile acids; cholic acid; viabilita buněk; MCF-7 Cells